Connected cars – the next targe tfor hackers. (November 2015) - Ring, Tim
Abstract : Not so long ago, the idea of us all motoring around in driverless and crash-proof cars seemed about as believable as the 1960s Jetsons cartoon family zipping around in their Aerocar. But today's petrol-heads are rapidly getting used to the fact that next-generation 'connected' cars, whose wifi-like crash-avoidance systems beacon out to track nearby vehicles, will start appearing on our roads in 2017/18. Driverless and crash-proof cars are no longer science fiction but fact. They promise a revolution in car safety, saving hundreds of thousands of lives a year. But most of these cars will be sharing data via the web. This raises real security concerns. But just how real is this car hacking threat and how much is hype? Tim Ring finds out, and reports on what security researchers are doing to push car makers to accelerate their drive to take car security seriously. He also asks what car drivers can do to protect themselves and their passengers.